Pengaruh Produk Ikan Sarden Merek Bantan terhadap Minat Beli Konsumen pada PT Sarana Tani Pratama di Jembrana, Bali - Nur Fajriana Miranti; Mariam Mariam; Andi Baso Adil Natsir (Jurnal Manajemen Kewirausahaan dan Teknologi, 2024)
The research method used is simple linear regression analysis through research instrument tests (validity and reliability tests), classical assumption tests (normality tests and heteroscedasticity tests), and hypothesis testing using the t test, as well as correlation tests and determination tests. The results of respondents' responses show that brand image on buying interest has a very good effect. Through the t test, it was obtained that the tcount was 3.426> ttable worth 0.374 with a significance value of 0.002, which is much greater than 0.05. The study shows that the brand image of Bantan brand sardines has a significant positive effect on consumer buying interest at PT Sarana Tani Pratama (Y 2.765 + 0.370 X). The t test shows t count = 3.426, t table = 0.374 with a significance of 0.002 which is <0.05 and the coefficient of determination = 0.509, meaning that brand image affects buying interest by 50.9%.